-9x-6=93

Simple and best practice solution for -9x-6=93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9x-6=93 equation:



-9x-6=93
We move all terms to the left:
-9x-6-(93)=0
We add all the numbers together, and all the variables
-9x-99=0
We move all terms containing x to the left, all other terms to the right
-9x=99
x=99/-9
x=-11

See similar equations:

| 29+w=60 | | 23=1/2x-7 | | 5/38=x/1,824 | | x(2-6)=16 | | 20+j=51 | | 68-a=34 | | F(x)=10(0.85) | | 4=(2.5/x) | | 4=2.5/x | | q-38=49 | | 115+x+121=132 | | 115+x+121=180 | | H(t)=-16t^2+73t+6 | | -4(7+x)=-72 | | 4x²+8x+4=100 | | 5x+4=2(x-1)=11.4 | | 0=-0.33x^2+0.84x+6 | | -2x2-x-1=0 | | 2(-3x+19)-16x=16 | | 34s+4s-25s+2s-14s=16 | | 8x+48=192 | | 5c+4c-5c+8c=48 | | 3x+3x+10=-20 | | 3(x–2)+2x=-2x-3 | | -2+3x+13=3(2x+1) | | 11x-20-12x=-14x+6 | | 48x-17x-12x=19 | | 54=y/9 | | 15u+u-4u-9u+9u=36 | | X/3.11=x-233 | | 15b-4b-2b+b=20 | | -5(6x-14)=-13x+2 |

Equations solver categories